The self-study tutorial for otorhinolaryngology - Троян, Василь Іванович; Нікулін, Михайло Іванович; Нікулін, Іван Михайлович; Костровський, Олександр Миколайович; Troyan, V. I.; Nikulin, M. I.; Nikulin, I. V.; Kostrovsky, O. M. (My University, 2012)
The speciality of Ear, Nose and Throat,now better known as Otolaryngology:Head and Neck Surgery, stands at cross-roads with several other specialities and subspecialities such as neurology, neurosurgery, oncologic surgery, ophthalmology,paediatrics, plastic and reconstructive surgery, respiratory medicine and critical care,gastroenterology, allergy and immunology. The boundaries between these specialities and ours are indistinct and frequently transgressed.This has also led to the development of several subspecialities(better called superspicialities) within Otolaryngology thus giving birth to Otology, Otoneurology, Paediatric Otolaryngology,Skull Base Surgery, Head and Neck Oncology, Endoscopic and Minimal Access Surgery, Laryngology and Phonosurgery. With advances in technology such as advace computer imaging techniques with 3D reconstructions, endoscopes, powered instrumentation, navigational surgery, lasers, intensity modulated radiotherapy, stereotactic radiosurgery, etc.patient care has greatly improved.This has also put a greater demand on new generations of medical students who should be introduced to these advancements.
Посібник з оториноларингології для самостійної роботи
Keywords: otolaryngology; unassisted student’s work